RESEARCH OF THE INNOVATIVE POTENTIAL OF THE PROJECT TEAM - Avdeeva , A. P.; Akopyan, L.S.; Yermolaeva, M. B.; Kokueva , Zh. M.; Lubovskiy, D.V. (Modern Psychology, 2021)
The relationship between the components of innovation potential (readiness for innovation, readiness to work in a team, experience in working in a project team) is studied using a specially developed questionnaire of role behavior in a team and a methodology for studying types of innovative behavior. Employees of industrial enterprises aged 19 to 40 years and work experience from 6 months to 22 years involved in innovative projects, as well as among students of a technical university took part in the research. It was shown that the most preferred type of innovative potential among employees with experience is the "moderator" type, and students more often choose the "opportunity seeker" type. The similarities and differences of both types are considered. It was shown that students, in comparison with employees of enterprises, overestimate their propensity to introduce radical innovations and, in general, their own determination in professional activity.